Severe adverse events during sirolimus "off‐label" therapy for vascular anomalies. Issue 8 (13th February 2021) - Rössler, Jochen; Baselga, Eulalia; Davila, Victoria; Celis, Veronica; Diociaiuti, Andrea; El Hachem, Maya; Mestre, Sandrine; Haeberli, Dario; Prokop, Aram; Hanke, Christof; Loichinger, Wolfgang; Quéré, Isabelle; et al.
Abstract: Objectives: Clinical studies have shown low toxicity and a favorable safety profile for sirolimus in vascular anomalies. Here, we describe severe adverse events (SAEs) observed during "off‐label use" for vascular anomalies. Methods: We performed a retrospective, multicenter chart review for SAEs during "off‐label" sirolimus therapy for vascular anomalies and analyzed these cases by a predesigned workflow. Results: We identified 17 SAEs in 14 patients diagnosed with generalized lymphatic anomaly ( n  = 4), Gorham–Stout disease ( n  = 2), central conducting lymphatic anomaly ( n  = 1), lymphatic malformation ( n  = 4), tufted angioma ( n  = 1), kaposiform hemangioendothelioma ( n  = 1), and venous malformation in a patient with CLOVES syndrome ( n  = 1). Three patients presented two SAEs each. The age at initiation of sirolimus therapy was under 2 years ( n  = 5), 2–6 years ( n  = 5), and older than 12 years ( n  = 4). SAEs occurred during the first 3 months of sirolimus therapy ( n  = 7), between 3 and 12 months ( n  = 7) and after 1 year of therapy ( n  = 3). The most frequent SAE was viral pneumonia ( n  = 8) resulting in one death due to a metapneumovirus infection in a 3 months old and a generalized adenovirus infection in a 28‐month‐old child. Sirolimus blood level at the time of SAEs ranged between 2.7 and 21 ng/L. Five patients were on antibiotic prophylaxis. Conclusions: Most SAEs are observed in the first year of sirolimus therapy; however, SAEs can also occur after a longer treatment period. SAEs are potentially life threatening, especially in early infancy. Presence of other risk factors, that is, underlying vascular anomaly or immune status, may contribute to the risk of SAEs. Sirolimus is an important therapeutic option for vascular anomalies, but patients and physicians need to be aware that adequate monitoring is necessary, especially in patients with complex lymphatic anomalies that are overrepresented in our cohort of SAEs.